2009
DOI: 10.1007/s00044-009-9210-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous epidermal growth factor (EGF) on nonenzymatic antioxidant capacities and MPO activity of wound tissue

Abstract: Growth factors and cytokines are key regulators of the wound-healing process. Epidermal growth factor (EGF) plays a vital role during the process of wound healing. There are limited numbers of studies related to EGF implantation effects on oxidative stress in oral wound healing. The objective of this study was to investigate the effect of EGF on myeloperoxidase (MPO) activity and nonenzymatic antioxidant levels of oral wound tissue on different days. In this study, New Zealand male albino rabbits were used. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(31 reference statements)
2
0
0
Order By: Relevance
“…There were no significant alterations in the AA levels of EGF treatment when compared with the respective control. Consistent with our study, Peker et al reported that there was no change in the AA levels on oral mucosa with EGF treatment (49).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There were no significant alterations in the AA levels of EGF treatment when compared with the respective control. Consistent with our study, Peker et al reported that there was no change in the AA levels on oral mucosa with EGF treatment (49).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our study, Akbulut et al determined that there were no significant changes in the gastric GSH levels among all the groups with the EGF application 4. Also, Gulec et al reported that there were no alterations in the GSH levels with EGF therapy on the oral mucosa (49). In addition, Gupta et al found that GSH levels reduced during wound healing process for 14 days in immunocompromised rats (50).…”
Section: Discussionsupporting
confidence: 89%